Nurses’ Practices in Ensuring Child Safety in Hemodialysis Centers - Fadhil, Ammar A.; Ahjil, Zaid W. Ajil (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): This study’s objective is to evaluate nurses’ practice of patients’ safety in pediatric hemodialysis centers and find which sociodemographic data are affecting on their practices. Methods: A descriptive study has been applied to 48 nurses working at the hemodialysis centers at two Teaching Hospital in Salah Al-Din Governorate. The study was conducted on September 1st, 2023, to March 5th, 2024, utilizing non-probable sampling technique.A valid observational checklist by CDC used, consists of eight nursing responsibilities to evaluate nurses-based practice for patients` safety. The checklist was filled using a trichotomous scale with three evaluations: never (1 – 1.66), sometimes (1.67–2.33), and always (2.34–3). Data was entered and analyzed by SPSS program version 24. Results: Most participants nurses were female, the majority of them were between the ages of 25 and 30 years with 70.8%. Their work experience was about 1-3 years in nursing and the hemodialysis department with 45 % of total nurses. The findings of the current study revealed that nurses had a moderate practice of children safety with an overall mean score of (1.8762). The study showed that there was a statistical relationship between the nurses’ practicesand their nursing qualification. Conclusion: The study concluded nurses` practices for keeping children safety were inadequate. This inadequate level may lead to medical errors, complication, and financial burden for the family and health institutes. Recommendation: It is recommended that the hospitals implement specialized training programs relevant to patients’ safety to enhance nurses’ awareness of children safety and improve quality of nursing care for pediatric patients.